The Influence of Capital Structure and Profit Management on Income Tax on the Indonesian Stock Exchange (Empirical Study of Property Sub-Sector Companies) - Prasetyo, Budi (Lafadz Jaya Publisher, 2024)
This research aims to describe the influence of capital structure and profit management on income tax on the Indonesian Stock Exchange (empirical study of property sub-sector companies). The research method used is a descriptive method with a quantitative approach. The type of data used in this research is secondary data, where data is obtained by not making direct observations on the research object. The method used to support this research is a quantitative method and, in this research, a multiple linear regression model is used. The adjusted R square coefficient of determination, namely the Capital Structure Variable (X1), the Earnings Management Variable (X2), can explain the Income Tax Variable (Y) of 38.0%. Capital Structure has a positive and significant effect on Income Tax on the Indonesian Stock Exchange (Empirical Study of Property Sub-Sector Companies). Profit Management has a positive and significant effect on Income Tax on the Indonesian Stock Exchange (Empirical Study of Property Sub-Sector Companies). Capital Structure and Profit Management simultaneously have a significant effect on Income Tax on the Indonesian Stock Exchange (Empirical Study of Property Sub-Sector Companies).